Environmentally safe magnetic nanocatalyst for the production of biodiesel from Pongamia pinnata oil - Sami, Hafiza Qurat ul Ain; Hanif, Muhammad Asif; Rashid, Umer; Nisar, Shafaq; Bhatti, Ijaz Ahmad; Rokhum, Samuel Lalthazuala; Tsubota, Toshiki; Alsalme, Ali (Multidisciplinary Digital Publishing Institute, 2022)
Biodiesel is an alternative fuel in many developing and developed countries worldwide. Biodiesel has significant and numerous economic, environmental, and social benefits. However, the problem with conventional biodiesel production is the high industrial production cost, mainly contributed by the raw materials. Therefore, catalysts and feedstock are essential in increasing total biodiesel production rates and minimizing production costs. Magnetic nano-catalysts play a crucial role in heterogeneous catalysis due to their easy recovery, recyclability, excellent selectivity, and fast reaction rates, owing to their larger surface area. This research activity used heterogeneous magnetic nano-catalysts of ICdO, ISnO, and their modified form, to produce biodiesel. The synthesized nano-catalysts were made through co-precipitation and found quite efficient for transesterifying Pongamia pinnata oil. The effect of various parameters on biodiesel yield in the presence of prepared magnetic nano-catalysts has been studied. In the transesterification supported by ISnO, high yield, i.e., 99%, was achieved after 2 h of reaction time at 60 °C. The nano-catalysts were magnetically recovered and reused 4–5 times without any change in their activity. All the synthesized magnetic nano-catalysts performed SEM analysis. Each fraction of the produced biodiesel was assessed for different quality parameters, and the results were per ASTM standards. The components present in biodiesel produced from Pongamia pinnata oil were determined by GCMS.